Bedside Postpyloric Tube Placement and Enteral Nutrition Delivery in the Pediatric Intensive Care Unit. (28th January 2020) - Turner, Ashley D.; Hamilton, Susan M.; Callif, Charles; Ariagno, Katelyn A.; Arena, Anastasia E.; Mehta, Nilesh M.; Martinez, Enid E.
Abstract: Background: Enteral nutrition (EN) delivery may be more effective via a postpyloric (PP) feeding tube in critically ill children, but tube placement can be challenging. We aimed to describe PP tube placement and EN practices in a multidisciplinary pediatric intensive care unit (PICU) after the implementation of a nurse‐led bedside PP tube‐placement program. Methods: In a single‐center retrospective study, we identified 100 consecutive patients admitted to the PICU for >48 hours and for whom PP tube placement was attempted. Demographics, clinical characteristics, and details of PP tube placement and EN delivery were examined. Results: The study cohort had a median age (25th, 75th percentiles) of 3.89 years (0.55, 14.86); 66% were male. Respiratory illness was the primary diagnosis of admission (55%); 92% were on respiratory support. Risk of aspiration was the primary indication for PP tube placement (48%). Bedside placement was the initial technique for PP tube placement in 93% of patients (successful for 84.9%) and was not associated with serious complications. Eighty‐seven patients with a PP tube started EN and received a median 73.9% (12.3%, 100%) of prescribed energy goal on day 3 after EN initiation. PP EN allowed 14 of 39 patients receiving parenteral nutrition (PN) to transition off PN 7 days after EN initiation. Thirty‐five percent of EN interruptions were due to feeding‐tube dysfunction. Conclusion: Bedside PP tube placement is safe and feasible and allows for effective EN delivery and decreased PN use when applicable. Interruptions in PP EN due to tube malfunction are prevalent.